2007
DOI: 10.1146/annurev.cellbio.23.090506.123606
|View full text |Cite
|
Sign up to set email alerts
|

Wing Vein Patterning in Drosophila and the Analysis of Intercellular Signaling

Abstract: The positioning and elaboration of ectodermal veins in the wing of Drosophila melanogaster rely on widely utilized developmental signals, including those mediated by EGF, BMP, Hedgehog, Notch, and Wnt. Analysis of vein patterning mutants, using the molecular and genetic mosaic techniques available in Drosophila, has provided important insights into how a combination of short-range and long-range signaling can pattern a simple epidermal tissue. Moreover, venation has become a powerful system for isolating and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
280
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(287 citation statements)
references
References 132 publications
7
280
0
Order By: Relevance
“…During development, at least five different signaling pathways contribute to the establishment of vein and intervein territories: Hedgehog (Hh) signaling, bone morphogenetic protein (BMP) signaling, epidermal growth factor receptor (Egfr) signaling, Wingless (Wg) and Notch (N) signaling (Blair, 2007). dTip60 might be affecting any of these pathways, which would result in disturbed vein formation in the absence of dTip60.…”
Section: Effects Of Dtip60 On Wing Developmentmentioning
confidence: 99%
“…During development, at least five different signaling pathways contribute to the establishment of vein and intervein territories: Hedgehog (Hh) signaling, bone morphogenetic protein (BMP) signaling, epidermal growth factor receptor (Egfr) signaling, Wingless (Wg) and Notch (N) signaling (Blair, 2007). dTip60 might be affecting any of these pathways, which would result in disturbed vein formation in the absence of dTip60.…”
Section: Effects Of Dtip60 On Wing Developmentmentioning
confidence: 99%
“…In addition, we demonstrated that dPLZF overexpression induces the expression of vein-specific genes, such as rho and spitz, but not dpp and vn, which are required for the specification of vein fate. Rho signaling is required for the maintenance of vein cell fate and activates spitz (Blair, 2007;Lee, 2010) as well as the canonical Ras/ERK pathway via the activation of Egfr ligands (Roch et al, 2002). These results demonstrate that dPLZF is both a downstream component of the Ras/ERK pathway and an activator of Ras/ERK signaling during the development of the Drosophila wing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the rhomboid (rho), decapentaplegic (dpp), spitz, and vein (vn) genes perform crucial functions in vein specification during wing development (Blair, 2007). Indeed, rho-mediated hyperactivation of the MAPK pathway is required for vein formation throughout late larval and early pupal development.…”
Section: Drosophila Plzf Positively Regulates Wing Vein Differentiationmentioning
confidence: 99%
See 2 more Smart Citations